MENAKAR KEBIJAKAN FULL DAY SCHOOL (Studi Analisis Permendikbud No 23 Tahun 2017) - Muhammad Miftah (Jurnal Perspektif, 2018)
The full day school policy stipulated in the regulation of Educationand Culture Minister (Permendikbud) Number 23 of 2017 makesthe anxiety for the education activists who are not ready for theconsequences of this regulation. The anxiety of these educationalactivists began to disappear when Permendikbud No. 23 of2017 was abolished by a higher regulation, namely PresidentialRegulation (Perpres) No. 87 of 2017 which asserted that thefive-day school is an option rather than an obligation. In thisPresidential Decree, there is a gap for educational institutions torun the school hours in accordance with Permendikbud No. 23of 2017. It becomes interesting to be investigated in the realm ofeducational policy. This study analyzes how the emergence of apolicy in education, how to implement and evaluate the policiesthat have been applied especially Permendikbud No 23 of 2017about school hours, because there are still schools and madrasahthat use school hours in accordance with this permendikbud.